Growth effect of foreign direct investment: The role of labor market flexibility - Nurnaddia Nordin; Nurhaiza Nordin; Murni Yunus Mawar; Norzalina Zainudin (Universitas Islam Indonesia, 2019)
This paper deals with the role of the labor market in moderating the growth-effect of foreign direct investment (FDI) in developing countries. FDI has developed rapidly and become the main source of economic growth in developing countries. The purpose of this paper is to examine the role of labor market flexibility in mediating the impact of FDI on economic growth in developing countries. Panel threshold regression analysis proposed by Hansen (1999) is employed to assess the hypothesis of the study. Findings/Originality: The results provide the empirical finding of the role labor market in moderating the growth effect of FDI in developed and developing countries and fill this gap by assessing the role of labor market flexibility as an absorptive capacity in FDI-growth link in developing countries.